Design and fabrication of smartphone based single paper lateral flow assay for early detection of PCOS biomarker - Aniket Nandi; Yash Kumar Gaur; Divyanshi Thakur; Ekta Daweshar; Kalicharan Sharma (Biosensors and Bioelectronics: X)
Polycystic Ovary Syndrome (PCOS) is a multifactorial endocrine disorder with significant diagnostic challenges, especially in early stages. Current diagnostic methods are often complex, time-consuming, and dependent on laboratory-based infrastructure. This study presents the design and fabrication of a smartphone-assisted paper-based lateral flow assay (LFA) for the early detection of PCOS via the quantification of sex hormone-binding globulin (SHBG), a promising metabolic biomarker. Fluorescent nitrogen-doped carbon dots (CDs) were synthesized using a microwave-assisted method and conjugated with anti-SHBG antibodies via EDC/NHS chemistry. The LFA strips were constructed using Whatman filter paper, and hydrophobic barriers were drawn using permanent marker ink. A portable device equipped with a 365 nm UV LED and a smartphone camera enabled fluorescence detection. Recombinant SHBG antigen samples in phosphate-buffered saline (PBS) were tested across a concentration range of 80–4000 ng/mL. The system exhibited a strong linear response (R2 = 0.9677) between SHBG concentration and fluorescence intensity, with a calculated limit of detection (LOD) and limit of quantification (LOQ) of 2.68 ng/mL and 19.93 ng/mL, respectively. The analytical range of 80–4000 ng/mL corresponds to 0.8–42.1 nmol/L, covers the clinical diagnostic threshold of SHBG (<36 nmol/L). These results demonstrate the feasibility of a low-cost, point-of-care diagnostic tool for early PCOS screening. Further validation with clinical samples is necessary for real-world deployment.